Menggali Potensi Problem Based Learning: Definisi, Sintaks, Dan Contoh Nyata - Veronika Tiara; Ninawati Ninawati; Fransiska Liska; Rabiatul Alya; Yusawinur Barella (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The problem-based education model begins with posing a problem or posing a problem, focusing on disciplinary relationships, investigation, group collaboration, as well as creating work, demonstrating and solving the given case. This problem-based education is student-centered, where teachers only share a little data and students who want to be more active in solving problems. This problem-based education uses real (authentic) problems that are unstructured and open-ended as a context for students to improve their problem-solving and critical thinking skills, and at the same time build new knowledge. In contrast to conventional education where real problems are used as the implementation of concepts, problem-based education makes real problems a factor in students' learning process before they understand formal concepts. Keywords: Education, Based, Problems.